Transition Zone in Total Colonic Aganglionosis and Colorectal Hirschsprung Disease Shows a Similar Trend of Mucosal Innervation: Image Processing and Analysis (IPA) Study - Sheuka, Natallia; Cordeiro-Rudnisky, Fernanda; Whyte, Christine; Ahn, Sangtae; Boguniewicz, Ann; Lee, Hwajeong (American journal of clinical pathology, 2018)
Abstract Objectives Animal model studies suggest that total colonic aganglionosis (TCA) and aganglionosis involving the entire colorectum and up to 50 cm of the distal ileum may have a longer transition zone (TZ) than conventional colorectal Hirschsprung disease (HD), posing a challenge for surgical management. We compared mucosal innervation of TZ in TCA and colorectal HD by quantifying calretinin-positive mucosal nerve fibers using IPA. Methods Ten HD pull-through cases and one TCA case obtained during a stoma procedure were retrieved. Sections containing the TZ and normal ganglionated zone (NZ) were subject to calretinin immunohistochemistry. Immunostained slides were scanned and consecutive images were captured (×100 or ×200 in JPEG) to include TZ and distal NZ. Pixel count (PC), defined as the percentage of calretinin-stained pixels in the mucosa, was calculated using IPA as previously described, for each image. A linear regression line was fitted to the observed PC and the distance from the beginning of TZ for each specimen. The slope of the fitted line for the TCA case was compared to those for the HD group. Results A total of 277 images were captured (mean 25 per case). Two HD cases with low coefficients of determination (R2 < 0.3) were excluded from analysis. The median slope of the lines fitted to the observed PC against the distance from the beginning of the TZ was 0.0081 (range, 0.0023–0.0127) for the HD group and 0.0047 for the TCA case. The slope of TCA was within the slope range of HD group (Tukey’s method). Conclusion Similar to colorectal HD, mucosal innervation tended to increase along with the distance from the beginning of TZ in TCA. The slope for TCA was not significantly different from those for the HD group, implying that the length of TZ in TCA may not be much longer than conventional colorectal HD.